(untitled) (Research, Society and Development, 2021)
The theme of this research is "Coparenting and Stable Marriage: differences and requirements in the light of the Gugu Liberato case", with the general objective of analyzing the institute of coparenting in Brazil and its distinctions with the stable union, bringing as a lesson the case of presenter Gugu Liberato . The specific objectives of the study are: to conceptualize the institute of coparenting in the light of the Brazilian legal system; differentiate coparenting from stable union; point out the problems that may occur due to the new multiparental realities and examine the existing differences in the media case of presenter Gugu Liberato. The methodology applied was bibliographic research, having as source books, the IBDFAM website, current legislation, jurisprudential decisions regarding the subject of study and search for articles in the main databases, such as Google Academic and Capes Periodicals. The following were used as descriptors for the research: coparenting, stable union, Gugu Liberato and Family Law, with the main authors being Rodrigo da Cunha Pereira, Cristiano Chaves Farias, Maria Berenice Dias, Pablo Stolze, among others. In the end, it is concluded that the distinction of the coparental family from the coexistence family, in the specific case, may not be an easy task for the judge. However, it is necessary to analyze whether or not the requirements of a common-law marriage are present and, finally, to observe the existence of a co-parenting contract, disciplining the existing relationship, mainly in relation to the responsibility of each one with the offspring.